CONSUMERS’ PERCEPTION OF MUNICIPAL WATER QUALITY IN BARNAWA COMMUNITY OF KADUNA STATE, NIGERIA - Umar, H.O; Okareh, O.T; Adeleye, Adeniyi; Orifah, M.O; Amoo, A. O; Sabiu, N; Gana, S.A (FUDMA JOURNAL OF SCIENCES, 2020)
The study assessed consumers’ perception regarding the quality of municipal tap water distributed by the Kaduna State Water Board (KSWB) to the residents of Barnawa community of Kaduna state. Simple judgemental sampling was employed to select four hundred and twenty seven (427) households that were interviewed through questionnaire. Data obtained were analysed using descriptive statistics, chi square, t-test and ANOVA. Majority of the respondents (60%) reportedly receive intermittent municipal water supply while a sizeable proportion of the respondents (40%) reportedly received a constant municipal water supply. Again, a little above half of the respondents (52.1%) had a negative perception of the water quality. Majority (64%) of the respondents were not satisfied with the colour of the water. The association between consumer’s perception and use of tap water for drinking is statistically significant (χ2 = 4.345, p=0.04). Customers’ perception of the water quality affected their choice of the water for drinking but this did not affect their usage of the water for cooking. It is therefore recommended that KSWB should implement a system that ensures constant water supply to Barnawa community as intermittent water supply increases the risk of the water getting contaminated in the distribution system before reaching the final consumers.